Guide :

# i need the answer for these questions

Using Newton’s method, solve the system is xyz-x^2+y^2=1.34  x y-z^2=0.09 e^x+e^y+z=0.41  by newton method to obtain a solution near (1,1,1) use three iteration only

## Research, Knowledge and Information :

### Answer These Questions for TeleCert - Mass.Gov

Answer These Questions for TeleCert; ... Answer the following questions truthfully. ... To process your request for Direct Deposit you will need your Department of ...

### Marketers Need to Answer These 3 Questions Before Launching a ...

Marketers Need to Answer These 3 Questions ... Marketers Need to Answer These 3 Questions Before Launching a ... Without clarity on these basic questions, ...

### SOLUTION: i need answer for these questions - Computer ...

i need answer for these questions. Feb 21st, 2017 . Anonymous. Category: Engineering . Price: \$10 USD. Question description. ... Questions Archive. Blog. Accounting ...

### I need short answer for these questions. 1. What do you think ...

You can ask homework questions and get assistance. We have teachers in subjects of Math, Physics, History, ... I need short answer for these questions. 1.

### Need math help to Answer These Questions about ... - Studypool

Need math help to Answer These Questions about the volume of a cone

### Divorcing Women Need to Answer These Key Questions ... - Forbes

Aug 03, 2011 · Jeff writes “Divorce Dollars and Sense,” a weekly blog for Forbes.com about the ... Divorcing Women Need to Answer These Key Questions Before ...

### I need help to answer these questions. Thank you 1. Which of

I need help to answer these questions. Thank you 1. Which of. This answer was rated: ...

## Suggested Questions And Answer :

### I need the answers for this question please : show that 2^(1/4) (1-i) is a fourth root of -2?

I need the answers for this question please : show that 2^(1/4) (1-i) is a fourth root of -2? There is a problem here. If you take 2^(1/4) (1-i) to the 4th power you get: {2^(1/4) (1-i)}^4 = 2*(1-i)^4 And (1 – i)^4 = {(1 – i)^2}^2 = {1 - 2i + (i)^2}^2 = (1 – 2i – 1)}^2 = {-2i}^2 = -4 i.e. (1 – i)^4 = -4, not -1 as needed. Your expression would need to be 2^(1/4) (1-i)/√2 to give (-2) when taken to the fourth power. Assuming the typo ... Let z = -2 i.e. z = -2(cos(2nπ) + i.sin(2nπ)),   n = 0,1,2,3, ... or, z = 2(cos(π + 2nπ) + i.sin(π + 2nπ)),   n = 0,1,2,3, ... z = 2.e^(i.(π + 2nπ))   ---- Euler’s formula Taking the fourth root of z, as Z4 = z^(1/4) Z4 = (2)^(1/4).e^(i(π/4 + nπ/2)) Z4 = (2)^(1/4). (cos(π/4 + nπ/2) + i.sin(π/4 + nπ/2)) Letting n =  0,1,2,3 Z41 = (2)^(1/4). (cos(π/4) + i.sin(π/4)) = (2)^(1/4). (1/√2 + i. 1/√2) Z41 = (2)^(1/4)(1 + i)/√2 Z42 = (2)^(1/4). (cos(π/4 + π/2) + i.sin(π/4 + π/2)) Z42 = (2)^(1/4). (cos(3π/4) + i.sin(3π/4)) = (2)^(1/4). (-1/√2 + i. 1/√2) Z42 =  (2)^(1/4). (-1 + i)/√2 Z43 = (2)^(1/4). (cos(π/4  + π) + i.sin(π/4  + π)) Z43 = (2)^(1/4). (cos(5π/4) + i.sin(5π/4)) = (2)^(1/4). (-1/√2 –  i. 1/√2) Z43 = (2)^(1/4). (-1 –  i)/√2 Z44 = (2)^(1/4). (cos(π/4 + 3π/2) + i.sin(π/4 + 3π/2)) Z44 = (2)^(1/4). (cos(7π/4) + i.sin(7π/4)) = (2)^(1/4). (1/√2 –  i. 1/√2) Z44 = (2)^(1/4). (1 –  i)/√2 The final expression, Z44, shows that the 4th fourth root of (-2) is (2)^(1/4). (1 –  i)/√2, as required

### What is an integer repesented 25 feet above sea level

25 feet above sea level = +25 feet up from sea level = -25 feet down from sea level Note: Positive distance upward = up Positive distance downward = down Negative distance upward = down Negative distance downward = up

### 15 × [(112 - 2 × 5)2 + 14 × (37 - 26) ÷ 11] ÷ 5 - 4,605

15 × [(112 - 2 × 5)2 + 14 × (37 - 26) ÷ 11] ÷ 5 - 4,605 PLEASE HELP I HAVE A PROJECT ON STUDY ISLAND DO AND I REALLY NEED THE ANSWER ITS MY LAST QUESTION ON THERE AND IM DONE!! hELP IS NEEDED!! 15 × ((112 - 2 × 5)2 + 14 × (37 - 26) ÷ 11) ÷ 5 - 4,605 15 × ((112 - 10    )2 + 14 × (11)         ÷ 11) ÷ 5 - 4,605 Divide 11 by 11. 15 × ((102           )2 + 14 × 1                    ) ÷ 5 - 4,605 15 × ((102           )2 + 14                          ) ÷ 5 - 4,605 At this point, I'm going to make a hazardous assumption. You have used symbols to indicate both multiplication and division. However, the (102)2 does not include a symbol, so it PROBABLY means 102 squared. You COULD HAVE used ^2: ((112 - 2 × 5)^2 + 14 15 × ((102          )2 + 14                 ) ÷ 5 - 4,605 15 × ((10,404     )   + 14                 ) ÷ 5 - 4,605 15 × ( 10,418                                 ) ÷ 5 - 4,605 Here, you can divide the 15 by the 5.  3 × ( 10,418                                  )       - 4,605      ( 31,254                                    )       - 4,605 Answer: 26,649

### how come i cant answer anymore questions?

You can only answer 10 questions at a time. It means you have to wait 1 hour to able to answer questions again. That happen to me when I asked questions. I only had to add 10 questions at a time and wait 1 hour. It depends.

### OMG! I CANT FIGURE OUT HOW TO ANSWER THESE QUESTIONS!! SOMEONE TELL ME HOW!!

you need to say the questions first though and then people can answer it the questions you need help with

### factor the polynomial x2+9x+20

Problem: factor the polynomial x2+9x+20 i need to find the answer to thos qustion ,this question is pre-algebra ,i need to know how to factor ploynomials,what is a polynomial♦ A polynomial is an expression (as given in your statement) with one or more unknowns (in this case, x), co-efficients (the numbers that multiply the unknowns) and positive exponents (the 2 in x squared). Find factors of the constant (20) which add up to the co-efficient of x (9). x^2 + 9x + 20 = (x + 5) * (x + 4)

### round 58.7694 to the nearest tenth?

The 7 is in the tenths place.  The next digit to the right (6) is greater than or equal to 5, so the 6 rounds up. Answer:  58.8 . Whining and complaining = no one answers your question for 2  1/2 years.

### How do i resolve these?

The whole number is hours, so that's 1 hr. Subtract 1 to give 0.666... and multiply by 60=40 min. The seconds will be zero. To solve in general: example 2.345 hr. Whole number is hrs: 2. Subtract 2: 0.345, multiply by 60=20.7; whole number is minutes: 20. Subtract 20: 0.7, multiply by 60=42; this is the number of seconds, so the conversion is 2hr:20m:42s.   Multiply through by 4: 4C=s(t-d); divide through by s: 4C/s=t-d; add d to each side: (4C/s)+d=t so t=(4C/s)+d. The brackets aren't absolutely necessary, but they prevent ambiguity in interpretation.